Situation Report: Romania, 10 January 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu Criticizes CMEA Cooperation / by Anneli Maier Defense Minister Replaced / by Anneli Maier The New Food Program / by Paul Gafton Romanian Theater / by Crisula Stefanescu Historians Protest against Church Demolitions / by Dan Ionescu Writer Protests against Fanaticism and Intolerance / by Crisula Stefanescu Romania Stands Apart at the Budapest Cultural Forum / by Crisula Stefanescu Romanian-Hungarian Polemics Escalate / by Dan Ionescu Dispute with Bulgaria on Historical Issues / by Dan Ionescu Elena Ceausescu's Birthday / by Anneli Maier